1226 Prognostic impact of concomitant cardiac amyloidosis in aortic stenosis patients referred for transcatheter aortic valve implantation. (17th January 2020) - Ferreira, V; Aguiar Rosa, S; Rodrigues, I; Moura Branco, L; Galrinho, A; Rio, P; Patricio, L; Cacela, D; Ramos, R; Mendonca, T; Castelo, A; Garcia Bras, P; et al.
Abstract: Background: The prevalence of cardiac amyloidosis (CA) and aortic stenosis (AS) both increase with age. Transcatheter aortic valve implantation (TAVI) expands the number of patients (P) eligible for treatment of AS, emphasizing the need to understand the prevalence of CA in AS and its prognostic associations. Echocardiography with speckle tracking has emerged as a useful method to enhance the clinical suspicion and to provide prognostic information. Purpose: To estimate the prevalence of CA in P with severe AS referred for TAVI and to evaluate the impact of concomitant CA in prognosis. Methods: 94 consecutive AS P who underwent TAVI with maximum left ventricular wall thickness (LVWT)>12 mm were retrospectively identified. Clinical data, pre TAVI echocardiographic parameters and follow up (FU) data regarding all-cause mortality and MACE (including all-cause mortality, admission for heart failure, pacemaker implantation and stroke) were analysed. We registered apical sparing pattern in bull's eye plots (ASPB), calculated relative apical longitudinal strain formula (RALS) [average apical LS/(average basal LS + mid-LS)] and ejection fraction/global longitudinal strain (EF/GLS) ratio. Results: Mean age was 82.2 ± 5.8 years (Y), with 43 men (45.7%). 27.7% were in NYHA functional class II, 64.9% in functional class III and 7.4% in functional class IV. Median EF was 57 ± 15% and 26.6% presented EF < 50%. Suspected CA evaluated by ASPB was found in 39 P (41.5%) and RALS > 1 was identified in 22 P (23.4%). An EF/GLS ratio > 4.1 was obtained in 53 P (56.4%). Over a median follow-up of 13.4 ± 25.8 months, 28 deaths (29.8%) and 31 MACEs (33.0%) occurred. The presence of ASPB was associated with increased all-cause mortality (33.3% vs. 5.6%, p = 0.002), new bundle branch block and indication for pacemaker implantation (46.2% vs 37.0%, p = 0.05) and MACE (48.7% vs 22.2%, p = 0.01). All-cause mortality was also higher in P with RALS (31.8% vs. 12.5%, p = 0.04). P with GLS>-14.8% and ASPB had significantly worse prognosis regarding all-cause mortality (p = 0.003) and MACE (p = 0.007). Kaplan–Meier survival analysis showed that survival was significantly worse for P with ASPB (log-rank 0.002). With multivariate Cox regression analysis, ASPB was independently associated with all-cause mortality (HR = 4.49, p = 0.039). Conclusions: Suspected CA appears prevalent among patients with AS and associates with all-cause mortality. The importance of screening for CA in older AS patients and optimal treatment strategies in those with CA warrant further investigation, especially in the era of transcatheter aortic valve implantation.